(untitled) (Indian Journal of Animal Production and Management, 2018)
Goats are important component of livestock sector having adaptability to harsh climates which make them suitable for landless and marginal farmers. The contribution of goats is 3% of total milk production in India. Nutritionally goat milk is compared with bovine milk. In certain cases goat milk is preferred over bovine milk due to certain ailments viz: slow digestion, cholesterol deposition in blood vessels, increasing incidences of bovine milk allergy and lactose intolerance. When compared to cow and buffalo milk, easy digestion of goat milk has been attributed to its softer curd and small size of fat globules. Likewise lower content of αs1-casein and lactose in goat milk alleviates chances of milk allergy and lactose intolerance. Other proven benefits include prebiotic and anti-inflammatory properties of lactose derived oligosaccharides, mitigation of cancer and various terminal diseases. Goat milk possesses higher level of lactoperoxidase enzyme that breaks the pathophysiology of tuberculosis and so it is recommended for infants, old and convalescent people. However, higher amounts of short chain fatty acids present are partially responsible for the goaty flavour of goat milk.